A pilot study of natural formulation activity in the protection of stored wheat and barley against the stored-product insects - Paponja, Ivan; Rozman, Vlatka; Lucić, Pavo, inženjer agronomije; Liška, Anita (2021)
The stored-product insects are one of the major causes of losses in the stored cereals. Most of control measures still rely on a synthetic pesticide usage, but due to its negative side effects on the goods, human health, and the environment, there is an urgent need for an alternative control. A natural formulation based on the diatomaceous earth (DE) SilicoSec®, enhanced with the botanicals (essential oil lavender, corn oil, and bay leaves dust) and the silica gel was developed. The aim of the study was to test the activity of the developed formulation as a postharvest protectant of seed wheat and barley in the suppression Sitophilus oryzae (L.), Rhyzopertha dominica (F.) and Tribolium castaneum (Herbst). As a reference comparative value, the DE SilicoSec® was applied. Subsequent to the six months of storage under the simulated warehouse conditions, the formulation has completely suppressed the initial population development of all three tested insect species, both in wheat and barley. In wheat, a complete suppression was detected at the dose of 500 ppm against T. castaneum and 600 ppm against both R. dominica and S. oryzae. In barley, a complete suppression was detected at the doses of 500 ppm, 400 ppm, and 600 ppm against R. dominica, T. castaneum and S. oryzae, respectively. Conclusively, the results of this study indicate that the developed natural formulation based on the DE, botanicals, and silica gel was highly effective against the three major stored product insect species, providing a long-term safe storage of wheat and barley seeds.
Skladišni kukci jedan su od glavnih uzroka nastanka gubitka uskladištenih žitarica. Većina mjera zaštite i dalje se oslanja na primjenu sintetičkih pesticida, ali zbog njihova negativnoga utjecaja na robu, ljudsko zdravlje i okoliš, velika je potreba za alternativnim mjerama zaštite. Razvijena je prirodna formulacija na bazi dijatomejske zemlje (DZ) SilicoSec®, obogaćena botaničkim komponentama (eteričnim uljem lavandina, kukuruznim uljem i prahom lovorova lišća) te silikagelom. Cilj istraživanja bio je testirati djelotvornost razvijene formulacije kao zaštitnoga sredstva uskladištenoga zrna pšenice i ječma u suzbijanju Sitophilus oryzae (L.), Rhyzopertha dominica (F.) i Tribolium castaneum (Herbst). Kao referentna usporedna vrijednost korištena je DZ SilicoSec®. Nakon šest mjeseci čuvanja u simuliranim skladišnim uvjetima, formulacija je u potpunosti suzbila razvoj početne populacije svih triju testiranih vrsta kukaca u pšenici i u ječmu. U pšenici je potpuna inhibicija postignuta pri dozi od 500 ppm kod T. castaneum te pri dozi od 600 ppm kod R. dominica i S. oryzae. U ječmu je potpuna inhibicija postignuta pri dozama od 500 ppm, 400 ppm i 600 ppm kod R. dominica T. castaneum i S. oryzae. Zaključno, rezultati ovoga istraživanja ukazuju na vrlo visoku učinkovitost razvijene prirodne formulacije na bazi dijatomejske zemlje, botaničkih komponenata i silikagela protiv triju glavnih vrtsa skladišnih kukaca, osiguravajući dugotrajnu zaštitu uskladištenoga zrna pšenice i ječma.
Bibliografija: 37 jed.
Summary ; Sažetak.
Keywords: Pšenica -- Ječam -- Žitarice -- Skladištenje -- Skladišni kukci -- Dijatomejska zemlja